Bulusan eco-tourism park/resort - Relativo, John Paul E. (Manila : National University, 2003)
Bulusan Lake is a local term, which means a converging point of water from various sources. The bikol root word "BULOS" means to flow, Bulusan means a place where water passes of flows. Bulusan was organized as a barrio of Casiguran in 1630 and became a pueblo civil in 1631. However, there are no records available of the town's civil government executives before 1760. This is so perhaps, because the town had not yet attained his legal status as a principalia of under the Province of Albay.
Title page -- Letter of endorsement -- Jury's Approval sheet -- Dedication -- Preface -- Acknowledgement -- Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Terms of references -- Chapter IV. Design framework -- Chapter V. Analysis and presentation -- Chapter IV. Conclusion and recommendation.
Includes bibliographical references.